Basic Forehand Analysis of Students of SMP Negeri 5 Central Maluku - Maxi D. G. Leuwol; Welhelmina Unmehopa; Jonas Solissa (Peneliti.net, 2023)
This research aims to determine the skill level of playing table tennis in students of SMP Negeri 5 Central Maluku. This research is a type of analytical research. The population in this study were 30 students of class VII2 at SMP Negeri 5 Central Maluku. Based on the results of data analysis, this study concluded that the level of forehand hitting ability of students at SMP Negeri 5 Central Maluku was in the very good category 0% (0 students), good 0% (0 students), while 43.33% (13 students), less 57.67% (17 students), very less 0% (0 students). Thus students of SMP Negeri 5 Central Maluku have a forehand skill level that is included in the poor category.